PPM ANGKRINGAN SATE AYAM - Mei - Indrawati; Woro Utari; Chamariyah Chamariyah; Risca Ayu Rachmania; Kresensia Darmawati (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
This Community Service program partner, Mrs. Jama'li, who is in the chicken satay business, is located in Lontar Village, Sambikerep District, Surabaya City. Problems faced by partners: 1) Packaging that still sees oil seeping from the spices; 2) The absence of financial records; 3) The absence of production planning; 4) There is no wider marketing effort; 5) The determination of the selling price has not been calculated correctly; 6) Cleanliness; and 7) Production equipment (fans) are obsolete. Solutions offered: training and assistance: 1) packaging; 2) financial management; 3) production planning; 4) product marketing; 5) determination of selling price; 6) sanitation; and 7) procurement of fans. The results of the activity: the implementation of training and mentoring 1) good packaging, now there is no longer visible seepage of spices in the package; 2) financial management, partners are able to make records of expenses and income from their business; 3) production planning, partners can begin to reduce the number of unsold satays; 4) product marketing, partners are already using online marketing; 5) determining the selling price of the product, partners can calculate the cost of production and consider the price of satay competitors; 6) sanitation, partners pay attention to the cleanliness of products, tools and places of business; and 7) a new fan is available. Mitra was able to increase the number of satays sold from 100 skewers to 200 skewers per day.